Aktivitas Tabir Surya Pada Formulasi GEL Mengandung Ekstrak Etanol Daun Kersen (Muntingia Calabura Linn) Secara In Vitro - Sineiwa Ipo Higyeungsi; Evi Nurul Hidayati; Joko Santoso (Jurnal Medika Nusantara, 2023)
The prevalence of breast cancer in the city of Surakarta was the second highest cancer prevalence in the province of Central Java in 2013, namely 678 cases, while in the city of Semarang as the first place there were 832 cases and the city of Magelang as the third place there were 348 cases. Kersen leaves (Muntingia Calabura L) have a high total flavonoid and phenol content so they can be used as a basic ingredient for making sunscreen gel. The aim of this research was to determine the sunscreen activity of a gel formulation containing ethanol extract of cherry leaves (Muntingia calabura L), the effective dosage, and the good quality of the preparation. This type of research uses quantitative analytical experimental methods. Kersen leaf ethanol extract sunscreen gel was made using Carbopol 940 base. Three formulas were made with a Carbopol base concentration of 1% and varying doses of cherry leaf extract 4%, 6%, 9%. The total flavonoid content of cherry leaves was 21.55 mg QE/g. The result of physical characteristics of FI (pH 4,82 ; Viscosity 250 dpas ; Spreadability 6,05 cm ; Adhesion 3,57cm), FII (pH 5,41 Viscosity 330 dpas ; Spreadability 5,79 cm ; Adhesion 4,43 cm), FIII (pH 5,84 Viscosity 360 dpas ; Spreadability 5,21 cm ; Adhesion 4,64 cm) and FIV (pH 4,63 ; Viscosity 170 dpas ; Spreadability 6,14 cm ; Adhesion 4,88 cm). The SPF values ??produced at extract concentrations of 4% (FI), 6% (FII), 9% (FIII) were 17.02; 34.74, and 40.09. The highest SPF value is found in FIII, namely 40.09, which is included in the ultra protection category with a cherry leaf extract concentration of 9%.